Activity-based costing (ABC) and its implication for open innovation - Patrícia Rodrigues Quesado; Rui Silva (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Activity-based costing system, commonly known as the ABC system, emerged as a costing method capable of overcoming the limitations of traditional costing systems in face of economic and technological developments, namely, the arbitrary and imprecise allocation of indirect costs from distortions in the imputation criteria. In the current context, the development of an adequate costing system is of extreme importance in organisations because they feel the need to properly manage the resources at their disposal and control their costs to achieve efficient and effective management. Thus, this study aims to analyse international publications on the activity-based costing system in recent years, identifying trends in evolution and future research opportunities. Based on bibliometric techniques, the outputs obtained in the Web of Science (n = 752) and Scopus (n = 1107) databases were analysed in bibliometrix R package to make a systematic mapping and review of the literature. After removing duplicates, we obtained a final output of 1419 articles. The analysis of these publications points to a growing trend in the publication of articles on ABC, highlighting publications in partnership and their dispersion in magazines from different areas. The bibliometric analysis carried out results on the authors' global research performance over time, and we highlighted the pioneering publications every five years and analysed the general evolution. When analysing based on publication authors over time, we highlighted the main research themes and countries where studies had been carried out. On the other hand, we also highlighted the collaborative network between institutions, authors, and countries over time.
Keywords: 650; activity-based costing; bibliometric analysis; systematic literature review; web of science